STRATEGI BERSAING PENGUSAHA KECIL SULAMAN/BORDIR DI KOTA PADANG - Abror, Abror (Fokus Ekonomi, 2006)
This research wants to know about competitive strategy that chosen by the Embroidery SME,s and want to know about the effect of sales volume, total asset and age of firm to the generic strategy. By using a survey research with 100 respondents, this research found the embroidery SME,s used cost leadership strategy as a competitive strategy and no effect of sales, age of firm and amount of assets to the chosen competitive strategy. It found that the embroidery SME,s in the position “stag in the middle”.  If the SME,s wants to get the suitable strategy, they have to fit the strategy with the current conditions of firm and it is better to used focus strategy as a competitive strategy. The last this research found no effect of three variables to the chosen competitive strategy. Keywords: Competitive Cost Leadership, Differentiation, Focus Strategy